2004
DOI: 10.4049/jimmunol.172.5.3011
|View full text |Cite
|
Sign up to set email alerts
|

A Type I IFN-Dependent Pathway Induced by Schistosoma mansoni Eggs in Mouse Myeloid Dendritic Cells Generates an Inflammatory Signature

Abstract: Schistosomes are helminth parasites that display a dual impact on the immune system of their hosts. Although the larval stage, also known as schistosomulum, appears to subvert the host defenses, the egg stage induces strong inflammatory reactions. Given the pivotal role of dendritic cells (DC) in initiating and regulating immune responses, we compared the distinct transcriptional programs induced in immature mouse DC by S. mansoni eggs or schistosomula. Although SLA abrogated the transcription of many genes im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 47 publications
6
56
3
Order By: Relevance
“…Although until now the effects of live eggs on TLR activation have not been investigated, two independent studies have shown the implication of TLR2 and TLR4 in the recognition of certain egg components (17,18). Recently, using a genome-wide expression study, we found that live eggs induce a transcriptional program in myeloid DCs that culminates in the production of many IFN-induced inflammatory gene products (16). In the present study, we have taken a genetic and molecular approach to identify the TLR members involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although until now the effects of live eggs on TLR activation have not been investigated, two independent studies have shown the implication of TLR2 and TLR4 in the recognition of certain egg components (17,18). Recently, using a genome-wide expression study, we found that live eggs induce a transcriptional program in myeloid DCs that culminates in the production of many IFN-induced inflammatory gene products (16). In the present study, we have taken a genetic and molecular approach to identify the TLR members involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Using high density oligonucleotide microarrays, we have recently demonstrated that the egg stage of the metazoan parasite Schistosoma mansoni activates the transcription of many genes in myeloid DCs including those encoding cell surface markers (CD40 and CD86), inflammatory (TNF-␣), and immunoregulatory (IL-12p40) cytokines as well as ISGs (16). This signature is highly evocative of a TLR dependence.…”
Section: Dcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of TLRs by pathogens is the main pathway by which DCs become activated (42)(43)(44). We have shown recently that schistosome eggs activate DCs in vitro to mature and to produce immunostimulatory factors, including IL-12, via TLR2 and TLR3 (38,45). To check the potential involvement of these TLRs, WT, TLR2, TLR3, or double TLR2/TLR3-deficient DCs were sensitized with live eggs, and their ability to activate LMCs in vitro was then assessed.…”
Section: Inkt Cell Activation Does Not Require Tlr Engagement In Dcs mentioning
confidence: 99%
“…Carcinoma of the bladder is a long-term sequela of chronic infection. 21,[31][32][33] Bladder cancer is one of the most severe complications of chronic schistosomiasis. Case report studies indicate that individuals with schistosomiasis may develop bladder cancer earlier than uninfected people.…”
Section: Schistosoma Haematobium and Its Association With Squamous Cementioning
confidence: 99%